2019
DOI: 10.3390/biom10010067
|View full text |Cite
|
Sign up to set email alerts
|

Robust Prediction of Single and Multiple Point Protein Mutations Stability Changes

Abstract: Accurate prediction of protein stability changes resulting from amino acid substitutions is of utmost importance in medicine to better understand which mutations are deleterious, leading to diseases, and which are neutral. Since conducting wet lab experiments to get a better understanding of protein mutations is costly and time consuming, and because of huge number of possible mutations the need of computational methods that could accurately predict effects of amino acid mutations is of greatest importance. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Thus, these results clearly indicate the cumulative effects of these three sites. It has previously been found that combined mutations are more beneficial to the stability improvement of proteins than single point mutations [28]. [24].…”
Section: Protein Structure Modeling and Analysis Of Intramolecular In...mentioning
confidence: 99%
“…Thus, these results clearly indicate the cumulative effects of these three sites. It has previously been found that combined mutations are more beneficial to the stability improvement of proteins than single point mutations [28]. [24].…”
Section: Protein Structure Modeling and Analysis Of Intramolecular In...mentioning
confidence: 99%
“…Hence, researchers have long sought to develop tools for accurate in silico prediction of enzyme thermostability. Accordingly, many tools have been developed over the past two decades to predict the enzyme melting temperature ( T m ), the change in thermodynamic stability (ΔΔ G ) upon point mutations, or the optimal growth temperature (OGT) of the source organism. Unfortunately, for prediction purposes, higher OGT or thermal stability does not necessarily indicate substantial catalytic activity at high temperatures. , Hence, a tool that directly predicts the optimal catalytic temperature ( T opt ) of enzymes is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, researchers have long sought to develop tools for accurate in silico prediction of enzyme thermostability. Accordingly, many tools have been developed over the past two decades to predict the enzyme melting temperature (Tm), 1-3 the change in thermodynamic stability (∆∆G) upon point mutations, [4][5][6][7][8][9][10][11][12] or the optimal growth temperature (OGT) of the source organism. [13][14][15][16][17][18][19][20][21] Unfortunately, for prediction purposes, higher OGT or thermal stability do not necessarily indicate substantial catalytic activity at high temperatures.…”
Section: Introductionmentioning
confidence: 99%